2009
DOI: 10.1177/1538192708330232
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Waves of Social and Political Capriciousness: Inspiring Perspectives From DREAM-Eligible Immigrant Students

Abstract: This article examines the psychological and sociological impacts of the proposed Development, Relief, and education for Alien Minors (DReAM) Act and instate tuition legislation on DReAM-eligible students in the Midwestern United States. The researchers sought to capture the lived experiences of undocumented immigrant students through their rich interpretations of current immigration policy and how participants described their situation, their identity, and their dreams in relation to the volatility of their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Others have shown that ISRT policy can also have an empowering effect on undocumented students to mobilize and become more civically engaged (Morales et al 2009;Pérez Huber and Malagón 2007). While many proponents of restrictive policies often call ISRT policies ''un-American'' by arguing such policies are detrimental to US citizen students, this research helps further debunk this argument by demonstrating that ISRT policies may promote more egalitarian views toward undocumented immigrants among US citizen students.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that ISRT policy can also have an empowering effect on undocumented students to mobilize and become more civically engaged (Morales et al 2009;Pérez Huber and Malagón 2007). While many proponents of restrictive policies often call ISRT policies ''un-American'' by arguing such policies are detrimental to US citizen students, this research helps further debunk this argument by demonstrating that ISRT policies may promote more egalitarian views toward undocumented immigrants among US citizen students.…”
Section: Discussionmentioning
confidence: 99%
“…Coronado, 2010; Pérez Huber & Malagón, 2007) as well as characteristics of resiliency and hope (Morales, Herrera, & Murry, 2011;Pérez, Espinoza, Ramos, Coronado, & Cortés, 2010). These studies make a critical contribution to understanding the experiences of undocumented Latina/o students who have achieved college entry despite the institutional and federal barriers they face.…”
mentioning
confidence: 97%
“…There is a large body of research on traditionally underrepresented students' access to and attainment in college. However, in this set of literature, sociologists tend to focus on categories other than linguistic background, such as race or ethnicity (Deil‐Amen & Turley, ; Kao & Thompson, ), Latinos (Arbona & Nora, ; Callahan, ; Swail, Cabrera, Lee, & Williams, ), socioeconomic status (Bowen, Kurzwell, & Tobin, ; McDonough, ; Walpole, ), first‐generation college students (Nuñez & Cuccaro‐Alamin, ; Pascarella, Pierson, Wolniak, & Terenzini, ), and undocumented immigrants (Morales, Herrerra, & Murry, ). Although ELLs may be subsumed under one or more of these categories, they are rarely studied in their own right.…”
mentioning
confidence: 99%